2008
DOI: 10.1021/bi702085z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Quantitative Activation of Chlamydia trachomatis Ribonucleotide Reductase by Hydrogen Peroxide

Abstract: We recently showed that the class Ic ribonucleotide reductase (RNR) from the human pathogen Chlamydia trachomatis ( Ct) uses a Mn (IV)/Fe (III) cofactor in its R2 subunit to initiate catalysis [Jiang, W., Yun, D., Saleh, L., Barr, E. W., Xing, G., Hoffart, L. M., Maslak, M.-A., Krebs, C., and Bollinger, J. M., Jr. (2007) Science 316, 1188-1191]. The Mn (IV) site of the novel cofactor functionally replaces the tyrosyl radical used by conventional class I RNRs to initiate substrate radical production. As a first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
48
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 43 publications
8
48
0
Order By: Relevance
“…Features-EPR signals were detected of Mn(II)Fe(II) and Mn(III)Fe(III), as previously observed (27,32,71). The Mn(IV)Fe(IV) state attributed to a precursor of Mn(III)Fe(III) in Refs.…”
Section: Mn-fe Electronicsupporting
confidence: 80%
“…Features-EPR signals were detected of Mn(II)Fe(II) and Mn(III)Fe(III), as previously observed (27,32,71). The Mn(IV)Fe(IV) state attributed to a precursor of Mn(III)Fe(III) in Refs.…”
Section: Mn-fe Electronicsupporting
confidence: 80%
“…The tyrosyl radical is believed to be a target for direct reactions with radical scavengers, such as NO, and the underlying reason for avoiding the tyrosyl radical may be to produce a system that is more resistant to radical scavengers. 58,107 In both cases, it appears that Nature has devised a truly 21 (42) group, establishes R2-like proteins as di-metal substrate-converting catalysts with interesting implications for both academy and industry.…”
Section: Discussionmentioning
confidence: 99%
“…The recent identification and characterization of the R2 subclass found in Chlamydia (27) suggested that the class Ic RNR may represent an adaptation of the enzyme that confers increased resistance to poisoning by reactive nitrogen and oxygen intermediates, such as NO (21,30), to which intracellular pathogens are exposed during the course of infection. The class Ic R2 is the only small RNR subunit found in Chlamydia and other organisms, and it associates with a class Ia-type large subunit (NrdA) to form a functional enzyme (27).…”
Section: Discussionmentioning
confidence: 99%
“…(16). The biochemical characteristics of the chlamydial class Ic RNR (30) and the predicted lifestyle of M. tuberculosis suggest that NrdB may serve a specialist function in dNTP supply under conditions of nitrosative stress. The class II RNR-encoding gene nrdZ belongs to the regulon of "dormancy" genes controlled by the DosRST two-component regulator system and induced by hypoxia and low-dose NO (51,63) but is dispensable for growth and survival in mice (16).…”
mentioning
confidence: 99%